Caracterização físico-química e estudo do escurecimento enzimático em produtos derivados de açaí (Euterpe oleracea Mart.) - Paula, Gabriela Almeida de (2007)
The aim of this work was to detect oxidative enzyme activities (polyphenoloxidase and guaiacol peroxidase) in pulp, tropical juice and clarified juice of açaí fruit as well as to make a physicochemical and chemical characterization in these products. It was used as a raw material for this study type C açaí pulp (Euterpe oleracea Mart.) (8% of total solids) obtained from Fortaleza local market (Ceará-Brazil). The açaí tropical juice was prepared using 30% of the treated pulp with 0.1% of Cytrozym- Ultra L (v/v), obtained a juice with 1,260 Brix. The clarified juice was processed (1,030Brix) using 4% chitosan solution as clarifying aid and after that it was filtered. It was carried out a physicochemical and chemical characterization of pulp, tropical juice and clarified juice and was detected PPO and G-POD activities. A Statistical difference was occurred at the level of 5% of significance between the elaborated products with regarding to all the physicochemical and chemical parameters studied, with exception to the acidity. The tropical and clarified juice had not differed statistically (p≤ 0,05) with regarding to minerals analyzed, with exception manganese. The statistical analyses of the average values of the PPO activities did not find statistical differences to the level of 5% of probability among the three products. On the other hand, in relation to G-POD it was find a statistical difference (p≤0,05%) between the clarified juice and the pulp and tropical juice. The açaí clarified juice presented a low PPO activity due to the application of thermal treatment as well as the citric acid addition for maintenance of the color juice. However, a high activity of G-POD was detected in clarified juice possibly due to the dark pigment interference from non enzymatic and enzymatic reactions in wave length used for detection of tetraguaiacol.